Gamification - application of games in marketing and marketing education - Kenéz, András (The Hungarian Journal of Marketing and Management, 2019)
OBJECTIVE OF THE ARTICLE Gamification is the use of game elements and game design techniques in non-game contexts. There are more and more examples of its application in the fields of education, management and marketing. Scientific examination of the topic started in the marketing, management and psychology literature, and soon after the first books on gamification were published and university courses were launched. Among the first users, remarkable companies can be found (Microsoft, Nike), and many experts forecast a significantly increasing trend supported by the development of smartphone market. In my paper, I discuss the definition and the application opportunities of gamification based on literature and also present an example from the field of education. I used gamification in the marketing research course at Edutus College. This course was based on practical knowledge and the evaluation consist of a series of assignments - therefore usage of gamification was pretty obvious for this course. I had used more game techniques not only the points and levelling up in grading, which was the most frequent application of gamification in the field of education in Hungary. METHODOLOGY Descriptive case study. MOST IMPORTANT RESULTS I argue that the application of gamification can improve the activity of students and also helps them in continuous learning though it requires a lot of extra work from the teacher. We can expect the spread of gamification in the field of HR, education, and trainings or any other non-motivating activities can be boosted by it - though its efficiency would decrease it is loses its novelty. Adding fun elements to tasks seems to be an excellent way to motivate, to reach engagement. Gamification is a worthy of note trend of marketing.